Fast and Mobile Cataract Detection by Applying Line Laser Eye Illumination - Fehler, Nicole; Haag, Robin; Messias, Andre; Hessling, Martin (Jurusan Teknik Elektromedik, Politeknik Kesehatan Kemenkes Surabaya, Indonesia, 2024)
Cataract is observed when the eye lens becomes opaque. This condition causes blurred vision and is the main cause of blindness worldwide. Cataract diagnosis is usually performed during ophthalmologist examination using a slit lamp, which requires expertise, is expensive and bulky. In this study, we present a small handheld illumination setup for cataract detection. Ex-vivo porcine eyes are investigated to determine whether colored line lasers, 450 nm (blue), 520 nm (green) and 650 nm (red), which shine obliquely into the eye, are principally suited for detection of the Y shaped suture cataract and of cold cataract, respecting exposure limits of EU guideline 2006/25/EC. Camera images of the cataract exhibited good results under illumination with all line lasers. Observations with the physician’s eye led to an even better diagnosis of cataract. Generally, green laser light illumination was the best choice for cataract detection. With red laser light illumination, it was also possible, but least suitable for this purpose. With this method, line lasers are a good choice for cataract identification, as cataract can be detected quickly and without much effort. This type of line laser illumination of the eye is safe and both types of cataracts are detectable with all wavelengths. For the human eye, a further development of this system is conceivable.